Fundamentals of Entrepreneurship (ENT300) Business Plan: Rainbowlicious / Jeslinna Julan Tungki - Tungki, Jeslinna Julan; Jaya, Nurul Aini Farahin; Tin, Sheanie; Martin, Catherine; Francis, Fiona Stella; Kendawang, Sanganwati (2017)
First of all, the idea was founded by the seven partners. They are General Manager, Marketing Manager, Administration Manager, Operation Manager and Financial Manager. Inspired by the tourist that always praising our places in order to open up a business like ice¬ creams. They said, our place are suitable and strategic to make some businesses. Besides, our country is the most peace and beautiful places for other tourist and also people inside the country that can go for vacation. There are many places that people can go for travel such Port Dickson, Cameron Highland, “Gunung Kinabalu” and others. Furthermore, as we know Malaysia is the one of country that always getting problems with air pollution that can cause of haze. So that, we have to come out with something new that can reduce the pressure of heat especially for our body. This ice-cream is suitable for all people around the world. We can guarantee that our ice-cream is good and healthy for all stage of ages because it is less sugar compare to other ice-cream products. Moreover, our ice-cream will be taste delicious without adding any food colouring. Moreover, our customers also can enjoy their ice-cream because our dessert shop are provide comfortable facility such as air conditioning and Wi-Fi. This facilities can attract many people to visit our dessert shop. Nowadays, internet network is the most importance to communicate with one another especially for those doing business inside or outside the country. Finally, we expect to increase the number of customers and gain more profits in doing ice¬ cream business. The aim is to be well known especially to people in Mukah Sarawak and all people around the world. We hope in the future we will have excellent records in our cuisine and open more dessert shop in other places.